Clause combining in ancient Greek narrative discourse : the distribution of subclauses and participial clauses in Xenophon's Hellenica and Anabasis - Buijs, Michel. (Mnemosyne, Supplements, 2005)
This study describes the usage of subclauses and participial clauses in Xenophon's Hellenica and Anabasis , with additional examples from other texts, using a text grammar-oriented approach, which can map more factors underlying the distribution of these clauses, and offers a more satisfactory explanation of a larger number of instances than is possible using the traditional sentence-level approach. The discourse-analytic description of the different clause types focuses on how relations are coded by means of subordinating conjunctions, the differences in form and function as discourse boundary markers between preposed, sentence-initially placed subclauses and participles, and the differences between clause types with respect to the information ﬂow in on-going discourse. The discussion of many examples from the work of Xenophon makes this book interesting for both linguists and classical philologists.